What Was Protected? Measuring India's Tariff Barriers 1968-1992 - Ira N. Gang; Mihir Pandey (Rutgers University, Department of Economics, 1998)
This paper investigates the inter-industry structure of production in India. It examines the structure of protection, asking how much protection each industry receives. We calculate, compare and analyze several measures of trade protection across agricultural, manufacturing and service industries. Nominal protection levels for both realized and nominal (published) tariff rates are calculated. Balassa and Corden measures of effective protection are constructed using both of these tariff rates. The focus is on highlighting the properties of each measure and on the difficulties of choosing a single measure of protection. The results show that protection levels were high when nominal tariffs are used as the basis of measurement, supporting earlier studies. A number of sectors exhibit negative effective protection rates, however, when realized tariff rates are used. In addition, the latter measure shows a greater variability and a different ranking of sectors as compared to the nominal tariff based measure.
Keywords: 330